A comprehensive review of recent advances in optimal allocation methods for distributed renewable generation - Tercan, Said Mirza; Demirci, Alpaslan; Unutmaz, Yesim Esra; Elma, Onur; Yumurtaci, Recep (INST ENGINEERING TECHNOLOGY-IET, 2023)
Distributed generation (DG) has a key role in enlarging the implementation of renewable energy resources (RES). However, the intermittent and uncontrollable nature of RES can lead to several severe power quality-related issues. Therefore, many efforts have been made to overcome these issues by optimizing DG sizes and locations. Hence, optimal DG allocation (ODGA) is significant for DG performance and provides advantages to the power system, such as improved power quality, voltage stability, reliability, and profitability. This study reviews recent ODGA studies eliminating the main DG integration problems. Often used ODGA methods have been categorized, and the main differences have been discussed, giving the details of features of optimization methods such as convergence performance and computational burden. A deep analysis for categorizing the objectives of ODGA has been done. In addition, optimization methods applied in ODGA studies have been presented by comparing the superiorities of algorithms and validated test network models. The objectives and significant findings of the ODGA applications are summarized with the advantages and disadvantages. It can be concluded that ODGA has a critical role in RES integration on the DG side and in reducing carbon emissions. This paper leads and provides a perspective for researchers working on recent ODGA methods.
Keywords: distributed power generation; optimization; resource allocation; POWER DISTRIBUTION NETWORKS; GREY WOLF OPTIMIZER; DISTRIBUTION-SYSTEM; OPTIMAL PLACEMENT; MULTIOBJECTIVE OPTIMIZATION; ALGORITHM; DG; INTEGRATION; PENETRATION; MANAGEMENT; Science & Technology - Other Topics; Energy & Fuels; Engineering